Diagnostic and therapeutic assessment by telephone electrocardiographic monitoring of ambulatory patients. Issue 6036 (11th September 1976) - Hasin, Y; David, D; Rogel, S
Abstract : The electrocardiograms of ambulatory patients have been monitored over the telephone by staff of the intensive cardiac care unit using equipment in the unit. Telephone monitoring is a useful way of diagnosing transient symptomatic arrhythmias and a reliable aid in supervising the patient's rhythm at the beginning or end of treatment. The doctor has direct contact with the patient at the time of his symptoms so that he can reassure or instruct him. This system costs relatively little in manpower and equipment and permits relatively long periods of follow-up. It is effective, however, only in symptomatic cases in which the rate or rhythm disturbances last long enough to be transmitted. Also important are the negative findings when the patient complains of symptoms and abnormal findings during routine telephone transmissions. Accurate detection of transient ischaemic changes seems to be less reliable, and further technical improvements are required.